Belts, roads, and regions: The dynamics of Chinese and Japanese infrastructure connectivity initiatives and Europe's responses - Werner Pascha (Asian Development Bank Institute (ADBI), 2020)
The paper argues that East Asia is setting the pace for the recent trend in regional and inter-regional integration, which is associated with multilateral infrastructure connectivity initiatives, like the "Belt and Road Initiative" (BRI) of the People's Republic of China and Japan's "Partnership for Quality Infrastructure" (PQI). After introducing key issues, the paper explains the logic behind the recently grown importance of such initiatives and analyzes concepts like the BRI and PQI against this background in more detail. While infrastructure connectivity initiatives promise to combine national political, economic, and multilateral public good aspirations beneficially, conflicts among them are also possible and even likely. The paper then deals with Europe's, and particularly the EU's, role in this dynamism. The EU was one of the early movers, with the establishment of the European Investment Bank for instance, but its mechanisms have so far not become pillars of a coherent and forceful political-economic strategy of the EU. The current European situation is rather one of reacting to a dynamic that other countries elsewhere have created. The paper introduces the 2018 Joint Communication "Connecting Europe and Asia: Building Blocks for an EU Strategy" in this context and finds it to be lacking in various ways. The paper ends with conclusions and policy recommendations on some of the options for developing a more forceful European strategy.
Keywords: F21; F55; H54; H87; L91; O19; O57; P45; 330; infrastructure investment; connectivity; East Asia; Europe; European Union; Belt and Road Initiative; People's Republic of China; Japan